Skeletal maturation and aerobic performance in young soccer players from professional academies - Teixeira, A. S.; Valente-dos-Santos, J.; Coelho e Silva, M. J.; Malina, R. M.; Fernandes-da-Silva, J.; Cesar do Nascimento Salvador, P.; de Lucas, R. D.; Wayhs, M. C.; Guglielmo, L. G. A. (International Journal of Sports Medicine, 2015)
The contribution of chronological age, skeletal age (Fels method) and body size to variance in peak velocity derived from the Carminatti Test was examined in 3 competitive age groups of Brazilian male soccer players: 10-11 years (U-12, n=15), 12-13 years (U-14, n=54) and 14-15 years (U-16, n=23). Body size and soccer-specific aerobic fitness were measured. Body composition was predicted from skinfolds. Analysis of variance and covariance (controlling for chronological age) were used to compare soccer players by age group and by skeletal maturity status within of each age group, respectively. Relative skeletal age (skeletal age minus chronological age), body size, estimated fat-free mass and performance on the Carminatti Test increased significantly with age. Carminatti Test performance did not differ among players of contrasting skeletal maturity status in the 3 age groups. Results of multiple linear regressions indicated fat mass (negative) and chronological age (positive) were significant predictors of peak velocity derived from the Carminatti Test, whereas skeletal age was not a significant predictor. In conclusion, the Carminatti Test appears to be a potentially interesting field protocol to assess intermittent endurance running capacity in youth soccer programs since it is independent of biological maturity status.